A1_7 Holes in the Sound - Davis, Yasmin; Drewes, Nora; Lomax, Thomas; Norman, Sarah (Physics Special Topics, 2020)
In this paper we investigated the effect of sound holes in electric guitars on the sustain based on our model of solid body and chambered body guitars. The resonant frequency of the air in the sound hole is found through the Helmholtz frequency, and if this is not too far from the chord it can dramatically reduce the sustain. We found that for the high E note the sustain is reduced by a factor of 100-300 as the body resonance approaches the note.